Book Review: Shankar Kumar Bhaumik, Principles of Econometrics: A Modern Approach Using EViews. (June 2017) - Maiti, Moinak
Shankar Kumar Bhaumik, Principles of Econometrics: A Modern Approach Using EViews, 2015, New Delhi: Oxford University Press, 496 pp., ₹795. ISBN: 978-0-19-809853-9